Isolation and Determination of Beta-Carotene in Carrots by Magnetic Chitosan Beta-Cyclodextrin Extraction and High-Performance Liquid Chromatography (HPLC). (24th July 2019) - Dai, Yunliang; Row, Kyung Ho
Abstract: Beta-carotene is a carotenoid with strong antioxidant activity that has been used in many areas and attracted significant attention. Among the articles reported, however, there are few examples of the convenient and eco-friendly use of magnetic chitosan biopolymers to extract beta-carotene. This paper reports the ultrasonic-assisted solid phase extraction of beta-carotene. The beta-carotene in carrot samples was extracted using synthesized magnetic chitosan beta-cyclodextrin biopolymers prior to high-performance liquid chromatography (HPLC) detection. Under the optimal conditions, the beta-carotene content of carrot was found to be 41.06 ± 0.02 μg/g. This newly developed method using magnetic chitosan cyclodextrin biopolymers is a promising method for the ultrasonic-assisted solid phase extraction of carotenoids from vegetables because the procedure is facile and rapid and the magnetic biopolymers can be removed using simple process.